Evaluation of the Impact of Governor-less Control on the Transient Response of Hydraulic Load Frequency Control Systems - Laksono, Heru Dibyo; Putri, Dhea Rahmadani; Muharam, Mumuh (Universitas Negeri Padang, 2025)
This study evaluates the transient performance of a hydraulic Load Frequency Control (LFC) system configured with a single controller and without a governor. The analysis focuses on rise time, peak time, settling time, and overshoot, using various controllers including PI, PD, PID, PDF, and PIDF. Simulation results indicate that eliminating the governor significantly enhances system responsiveness and reduces overshoot, particularly when using the PDF controller. Quantitative analysis shows that the PDF controller achieves 85% faster rise time (0.101s vs 0.607s for P controller) and maintains system stability with minimal overshoot (1.765% for PID vs 59.263% for P controller). This configuration enables for a more direct and efficient control response to load fluctuations, improving system stability. Thus, employing a single controller without a governor presents a promising alternative for frequency regulation in hydraulic LFC systems under dynamic load conditions. The findings of this study offer valuable insights for optimizing controller selection and configuration in practical implementations, providing guidance for engineers and researchers to enhance grid reliability, operational efficiency, and stability in various real-world hydraulic power system scenarios.